Effects of Different Junction Parameters on Junction Conductances of Crossed Metallic Carbon Nanotubes (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the effect of different junction parameters on the junction conductances  made of two crossed metallic carbon nanotubes. We have found that because of the intrinsic  asymmetries of the junction, forward and backward tunneling between one tube and the other  are unequal. Passing a current in one tube leaded to the development of non zero voltage  across the other one, a zero field Hall like conductance for the junction was found. We have  found that this zero field Hall conductance relates to the contact conductance of the junction.  The result also shows that the electronic properties of the junction sensitively depend on the  degree of matching between the tube lattices. This matching is controlled by the crossing  angel, which resulted in an intertube conductance that varied by an order of magnitude for  different angles. We have derived a tunneling matrix element that coupled the low energy  electronic states on the two tubes. The magnitude of the coupling was determined by the  intertube separation of the crossing angle. We have found that the intrinsic symmetries of the  junction created a discrepancy between the forward and backward hopping between the  tubes. Using Landauer-Buttiker formalism, we have calculated the different conductances of  the four terminal junctions. We have found that the contact conductance scaled inversely with  the zero field Hall conductance of the junction. We have also found that the two crucial  parameters in determining the conductance are the tube chiralities and the crossing angle. The  obtained results were found in good agreement with previously obtained results.